Liver Involvement in SARS-CoV-2 Vertically Infected Newborn: A Case Report - Stolfi, Ilaria; Conti, Maria Giulia; Marciano, Alessandra; Dito, Lucia; Natale, Fabio; Bartolucci, Monica; Cellitti, Raffaella; Regoli, Daniela; Ticchiarelli, Alessandra; Pangallo, Ida; Pagano, Federica; Ajassa, Camilla; et al. (Frontiers in Pediatrics, 2021)
Neonatal SARS-CoV-2 infection can occur antenatally, peripartum or postnatally. In the newborn clinical manifestations may vary including fever, respiratory, gastrointestinal and neurological symptoms. Most commonly, they are subclinical. We herein present a case of vertical transmission of SARS-CoV-2 presenting with liver injury, characterized by an increase in serum transaminases.